1989
DOI: 10.1038/ki.1989.106
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of low density lipoprotein with rat mesangial cells

Abstract: Hyperlipidemia may contribute to the pathogenesis of glomerular sclerosis. We therefore studied binding and uptake of low density lipoprotein (LDL) by cultured rat mesangial cells. In addition effects of LDL on PGE2 synthesis and cell proliferation were determined. At 4 degrees C mesangial cells bound [125I] LDL in a time- and concentration-dependent manner with half-maximal binding observed at 5 micrograms/ml of LDL protein. Binding was blocked by excess unlabeled LDL and by heparin. Uptake (binding plus inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…Table 3 shows that probucol decreased total cholesterol and LDL-cholesterol. Lipids play an important role in the pathogenesis of glomerular sclerosis 35,36) , and LDL was taken up by mesangial cells 37,38) . Thus, the LDL-cholesterol-lowering action of probucol may also contribute to the beneficial effects of probucol on diabetic nephropathy.…”
Section: Renal Dysfunction and Other Eventsmentioning
confidence: 99%
“…Table 3 shows that probucol decreased total cholesterol and LDL-cholesterol. Lipids play an important role in the pathogenesis of glomerular sclerosis 35,36) , and LDL was taken up by mesangial cells 37,38) . Thus, the LDL-cholesterol-lowering action of probucol may also contribute to the beneficial effects of probucol on diabetic nephropathy.…”
Section: Renal Dysfunction and Other Eventsmentioning
confidence: 99%
“…5 Mesangial and glomerular epithelial cells express low-density lipoprotein (LDL) receptors and are capable of endocytosis of bound LDL. 6,7 We and others have demonstrated that hyperlipidemia and diabetes cause accumulation of renal foam cells in animal models, 8 -10 and we recently demonstrated that lowering of lipid levels via dietary means limits progression of renal injury. 10 Increased renal deposition of apolipoproteins (apo) B and/or E is associated with increased mesangial cellularity, increased proteinuria, and increased severity of glomerulosclerosis in a variety of glomerular diseases in humans.…”
mentioning
confidence: 99%
“…The mechanism by which hypercholesterolaemia causes or aggravates glomerular injury is not known. Specific binding and uptake of LDL has been demonstrated in rat mesangial cells [18]. In human nephritic kidneys, glomerular epithelial and mesangial cells have been shown to express both LDL receptors and scavenger receptors [19].…”
Section: Discussionmentioning
confidence: 95%